Development of Documentary Video Learning Media to Improve Student Learning Outcomes in Invertebrate Materials - Aloysius Joko Susilo; Amin Retnoningsih; Saiful Ridlo (Journal of Innovative Science Education, 2023)
Invertebrate learning should present real objects of observation in the classroom or laboratory. The average learning outcomes of class X students of Senior high school (SMA MIPA) in the 2021/2022 academic year for Invertebrates material is 68 and only 38% achieve KKM or minimum completeness criteria is 70. The value of attitudes and skills of students is also not optimal. The purpose of this study was to analyze the characteristics, validity, practicality, and effectiveness of documentary video learning media on invertebrate material at SMA Negeri 1 Pulokulon, Grobogan Regency. This research is research and development (R&D). Documentary videos are validated by experts and practitioners. Practicality is determined by the responses of students and teachers. The effectiveness of video documentaries was tested with the Pretest-Posttest Control Group Design. Data on attitudes and skills of students were observed by providing an assessment with a rating scale and then an independent t test was carried out. Classical completeness was analyzed by descriptive percentage. the independent t test was used to test whether there was a difference in the posttest mean between the experimental group and the control class. The results showed that the Invertebrates video material was prepared by considering format, content, language, and media engineering aspects, so that it spurred students in discovery learning activities, namely: identifying problems, observing, collecting data, compiling data, communicating, and concluding. The learning device in the form of documentary video learning media on invertebrate material is declared valid in the very good category. Documentary video learning media on Invertebrates material are stated to be practical. with very positive criteria. Documentary videos on Invertebrates are effective on cognitive learning outcomes, attitudes, and process skills.